Romantización de la violencia. Caso: Película 365 días - Ribadeneira Muñoz, Mariana Belen (2020)
The research project was carried out in the Montalvo canton of Los Ríos Province, with the aim of identifying the degree of influence that the media has in the Romantization of gender-based violence bearing as reference the case of the film 365 days transmitted through Netflix,Inc which is considered one of the American Entertainment Companies with distribution of audiovisual content through an online platform or video service on demand by live broadcast that you can view your content around the world. The media is now a fundamental tool in people's lives, so a survey was conducted for the Women of the canton, the study of this case allowed to determine that the majority of the population of women are influenced by the media. The different media play a leading role in modern societies as they allow to inform, communicate, entertain, persuade, watch world events, conflicts, politics issues, sports, social events and many more.